Architectures for enterprise integration - Bernus, Peter; Nemes, L.; Williams, Theodore J. (published by Chapman & Hall on behalf of IFIP and IFAC, 1996)
"The 1990s have seen many large-scale efforts to transform companies into more agile and efficient global enterprises. An important lesson from the efforts in computer-integrated manufacturing and other businesses has been that enterpriseslike any other system - need to be properly designed and that methods to do this should become widely available and publicised. Architectures for Enterprise Integration describes the latest methods to guide enterprises and consultants, managers and technical personnel through a complete life-cycle of enterprise development." "This book is based on the findings of the IFIP/IFAC Task Force and presents a state-of-the-art review of enterprise architecture, including analysis and comparison of the three major architectural frameworks and methodologies; identification of the strengths and weaknesses of each methodology to enable users to select the approach which best suits their needs; a roadmap for the development of more complete methodologies by using existing ones." "This book is essential reading for all practising engineers and researchers in manufacturing and engineering management and will be of special interest to those involved in CIM and enterprise modelling and integration."--BOOK JACKET.